Predictive factors of severe infections in patients with systemic necrotizing vasculitides: data from 733 patients enrolled in five randomized controlled trials of the French Vasculitis Study Group. (28th November 2019) - Lafarge, Antoine; Joseph, Adrien; Pagnoux, Christian; Puéchal, Xavier; Cohen, Pascal; Samson, Maxime; Hamidou, Mohamed; Karras, Alexandre; Quemeneur, Thomas; Ribi, Camillo; Groh, Matthieu; Mouthon, Luc; et al.
Abstract: Objectives: Infections remain a major cause of morbidity and mortality in systemic necrotizing vasculitides (SNV). We aimed to identify factors predicting severe infections (SI) in SNV. Methods: Data from five randomized controlled trials (RCTs) enrolling 733 patients were pooled. The primary end point was the occurrence of SI, defined by the need of a hospitalization and/or intravenous anti-infectious treatment and/or leading to death. Results: After a median follow-up of 5.2 (interquartile range 3–9.7) years, 148 (20.2%) patients experienced 189 SI, and 98 (66.2%) presented their first SI within the first 2 years. Median interval from inclusion to SI was 14.9 (4.3–51.7) months. Age ≥65 years (hazard ratio (HR) 1.49 [1.07–2.07]; P =0.019), pulmonary involvement (HR 1.82 [1.26–2.62]; P =0.001) and Five Factor Score ≥1 (HR 1.21 [1.03–1.43]; P =0.019) were independent predictive factors of SI. Regarding induction therapy, the occurrence of SI was associated with the combination of GCs and CYC (HR 1.51 [1.03–2.22]; P  = 0.036), while patients receiving only GCs were less likely to present SI (HR 0.69 [0.44–1.07]; P  = 0.096). Finally, occurrence of SI had a significant negative impact on survival ( P <0.001). Conclusion: SI in SNV are frequent and impact mortality. Age, pulmonary involvement and Five Factor Score are baseline independent predictors of SI. No therapeutic regimen was significantly associated with SI but patients receiving glucocorticoids and CYC as induction tended to have more SI.